Phase transition in an exactly solvable model of interacting bosons - Gorunovich, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
In the formalism of the grand canonical ensemble, we study a model system of a lattice Bose gas with repulsive hard-core interaction on a perfect graph. We show that the corresponding ideal system may undergo a phase transition (Bose-Einstein condensation). For a system of interacting particles, we obtain an explicit expression for pressure in the thermodynamic limit. The analysis of this expression demonstrates that the phase transition does not take place in the indicated system.